2012
DOI: 10.1123/ijsc.5.1.87
|View full text |Cite
|
Sign up to set email alerts
|

“Patriots at Play”: Analysis of Newspaper Coverage of the Gold Medal Contenders in Men’s and Women’s Ice Hockey at the 2010 Winter Olympic Games

Abstract: This study compared how The Globe and Mail and The New York Times covered the Canadian and U.S. women’s and men’s ice hockey teams competing in the 2010 Winter Olympic Games. A content-analysis methodology compared the amount and prominence of coverage devoted to the women’s and men’s teams. Each newspaper provided more coverage of the men’s teams and to its own national teams, particularly in prominent locations. Textual analysis was used to analyze how the gendered themes intersected with national identity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 28 publications
2
34
0
1
Order By: Relevance
“…Pratt, Grappendorf, Grundvig, and LeBlanc (2008) examined newspaper coverage of the 2004 Summer Olympics and discovered that male athletes received more coverage in terms of column inches and were more likely to be featured on the front page of the sports section. Vincent and Crossman (2012) examined coverage of the Canadian and U.S. men's and women's hockey teams provided by The Globe and Mail and The New York Times during the 2010 Winter Olym pics and found that both media organizations provided more coverage to the men's teams. Because of the discrep ancies in coverage listed above, scholars have concluded that the media may have set an agenda that reinforced stereotypical portrayals of athletes (Billings et al, 2008;Billings & Eastman, 2003;Tuggle & Owen, 1999).…”
Section: Media Coverage Of the Olympicsmentioning
confidence: 98%
“…Pratt, Grappendorf, Grundvig, and LeBlanc (2008) examined newspaper coverage of the 2004 Summer Olympics and discovered that male athletes received more coverage in terms of column inches and were more likely to be featured on the front page of the sports section. Vincent and Crossman (2012) examined coverage of the Canadian and U.S. men's and women's hockey teams provided by The Globe and Mail and The New York Times during the 2010 Winter Olym pics and found that both media organizations provided more coverage to the men's teams. Because of the discrep ancies in coverage listed above, scholars have concluded that the media may have set an agenda that reinforced stereotypical portrayals of athletes (Billings et al, 2008;Billings & Eastman, 2003;Tuggle & Owen, 1999).…”
Section: Media Coverage Of the Olympicsmentioning
confidence: 98%
“…Vincent and Crossman (2012) found more than a 2:1 ratio favoring men within newspaper coverage of Olympic ice hockey; Coche (2012) found ESPN's internet coverage of the Australian Open yielded more than triple the hours for men's tennis than women's tennis; Turner (2014) studied SportsCenter, finding not only an ''almost complete lack of coverage'' of women's sports (pp. 16-17) but also that women were no more likely to occupy host, reporter, or coaching roles in 2009 than they were in 1999.…”
Section: Related Literaturementioning
confidence: 98%
“…The commentators produce a narrative of us/Norway and them/the opposition. As documented elsewhere (Vincent & Crossman, 2012) it is evident in the material that also contemporary women are symbolic bearers of national and masculine virtues. Furthermore, the Norwegian female handballers are metaphorically represented as managing not only team handball, but also other masculine contact-sports such as wrestling (Sisjord & Kristiansen, 2008).…”
Section: War At Last: Cultural Conceptions Of Sport As Warmentioning
confidence: 99%
“…Through the TV screen, the often hyper-masculine warrior narratives of male sports are glorified and broadcasted to wide audiences (Broch, 2011;Gee, 2009;Messner, Dunbar, & Hunt, 2000;Trujillo, 1995;Vincent & Crossman, 2012). Jordan and Cowan (1995, p. 729) accordingly argue that " [t]he mantle of the warrior is inherited by the sportsman".…”
Section: Sport Gender and The Mediamentioning
confidence: 99%
See 1 more Smart Citation